Irrigation blades and nitrogen doses in bean cultivation - Santana, Márcio José de; Assis, Matheus Pereira de; Trindade, Stephânia Martins; Kempen, Jan Cornelis van; Carneiro, Nicolly Urzedo (Revista Agrogeoambiental, 2021)
Irrigation makes it possible to increase productivity in bean crops, but if mishandled, it can increase production costs and promote the leaching of nutrients, especially nitrogen, a nutrient that is fundamental for the development of the crop. Given the above, the objective of this study was to evaluate the yield of common beans subjected to different doses of nitrogen and water depths in the region of Uberaba – MG, Brazil. The experiment was conducted at IFTM – Campus Uberaba, in randomized blocks, consisting of four levels of irrigation (deficits of 15 %, 30 %, and 45 % and a factor without water deficit) and four doses of nitrogen (50 kg ha-1, 100 kg ha-1, 150 kg ha-1, and 200 kg ha-1) applied in stage V4 of beans. The cultivar used was BRSMG Majestoso. There was no interaction between irrigation levels and nitrogen doses for the variables studied. Nitrogen doses influenced linearly only leaf nitrogen content. The water deficit of 9.72 % was favorable to achieve maximum grain yields and favors the number of pods per plant. The plant mass in R6, a mass of 100 grains, hydration, and thermal sum declined linearly with increased water deficit.